USES OF JUSTICE AND ARBITRATION OF DISPUTES IN THE OLD REGIME: EXPERIENCES IN THE HISPANIC MONARCHY - Mantecón Movellán, Tomás (Revista de Historia Social y de las Mentalidades, 2016)
By analyzing legal and political literature  referring to the Hispanic Monarchy as well as  by studying judicial cases and practices, this  article explains social uses of justice and ways  of settling conflicts in the Old Regime. This  research gives new perspectives on justice  as very much socially participated. At the  same time, by stressing this socially focused  perspective, this article shows the public peace  building as a broader phenomenon from which  it is frequently shaped from political history  and history of law, giving new perspectives  to reconsider the so-called historical judicial  or legal revolution in Old Regime Western  societies
Keywords: Uses of justice; Arbitration; Justice; Crime; Punishment; Grace; Hispanic Monarchy